Structural analysis with finite elements - Rugarli, Paolo, 1963- (Thomas Telford, 2010)
Structural Analysis with Finite Elements reveals the theory behind the finite element method as it relates to structural engineering and explains how to overcome commonly encountered problems and errors found in everyday structural modelling with finite element software.
Keywords: Structural analysis (Engineering); Finite element method.; elektronické knihy; electronic books